2018
DOI: 10.1111/are.13591
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and larval development of a hybrid between kelp grouper Epinephelus moara ♀ × giant grouper E. lanceolatus ♂ using cryopreserved sperm

Abstract: Hybridization was used to take advantage of desirable traits in offspring. In the present study, we applied the cryopreserved Epinephelus lanceolatus sperm into interspecific hybridization with E. moara. Successful hybridization between these two species was achieved and cultured in 23–24°C seawater (34‰). There was no difference in survival rate between hybrid (E. moara ♀ × E. lanceolatus ♂) and non‐hybrid (E. moara ♀ × E. moara ♂) at 24 hrs post hatch (HPH), but less hybrid (14.35 ± 8.02%) hatched than non‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The hatching time of RGGG was 27 hr 55 m ± 01 hr 45 m at 25°C, which was approximately 1 hr slower than that of RG (26 hr 57 m ± 00 hr 54 m; p > 0.05, Table ). According to previous studies, the hatching time of dusky grouper ♀ × white grouper ♂ and kelp grouper ♀ × giant grouper ♂ were 5 and 1 hr faster than that of the maternal species, respectively (Chen et al, ; Glamuzina et al, ). The hatching time of orange‐spotted grouper ( E. coioides ) ♀ × giant grouper ♂ did not differ from that of the maternal species (Kiriyakit et al, ).…”
Section: Parameters Of Embryonic Development and Hatchability Of Fertmentioning
confidence: 89%
See 4 more Smart Citations
“…The hatching time of RGGG was 27 hr 55 m ± 01 hr 45 m at 25°C, which was approximately 1 hr slower than that of RG (26 hr 57 m ± 00 hr 54 m; p > 0.05, Table ). According to previous studies, the hatching time of dusky grouper ♀ × white grouper ♂ and kelp grouper ♀ × giant grouper ♂ were 5 and 1 hr faster than that of the maternal species, respectively (Chen et al, ; Glamuzina et al, ). The hatching time of orange‐spotted grouper ( E. coioides ) ♀ × giant grouper ♂ did not differ from that of the maternal species (Kiriyakit et al, ).…”
Section: Parameters Of Embryonic Development and Hatchability Of Fertmentioning
confidence: 89%
“…In previous studies, the fertilization rate and hatching rate of goldblotch grouper ♀ × dusky grouper ♂ and dusky grouper ♀ × white grouper ♂ did not differ from those of the maternal species (Glamuzina et al, ; Kiriyakit et al, ), exhibiting the same tendency observed in this study. In contrast, the hatching rate of kelp grouper ♀ × giant grouper ♂ was 4.49%, which was significantly lower than that of the maternal species (64.35%; Chen et al, ).…”
Section: Parameters Of Embryonic Development and Hatchability Of Fertmentioning
confidence: 93%
See 3 more Smart Citations